2004
DOI: 10.1182/blood-2003-09-3043
|View full text |Cite
|
Sign up to set email alerts
|

Association of pharmacokinetic (CYP2C9) and pharmacodynamic (factors II, VII, IX, and X; proteins S and C; and γ-glutamyl carboxylase) gene variants with warfarin sensitivity

Abstract: We analyzed mutations of 7 vitamin K-dependent protein and cytochrome P450 2C9 genes in 45 patients and investigated whether any contribute to the large interpatient variability in the warfarin dose-effect relationship. Total clearance and daily dose, INR and INR/Cp, were used as pharmacokinetic and pharmacodynamic indexes, respectively. Patients were grouped by genotype based on a single polymorphism and combinations of polymorphisms. Among the 30 sequence variants identified, CYP2C9*3, 165Thr 3 Met of the fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
116
6
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(130 citation statements)
references
References 33 publications
3
116
6
1
Order By: Relevance
“…43 They showed that warfarin dose increased with the number of microsatellite (CAA)n repeats in intron 6. Interestingly, the GGCX SNP in intron 6 shows the same trend, but in our material a SNP in intron 2 was the best predictor of warfarin dose.…”
Section: Wadelius Et Almentioning
confidence: 99%
“…43 They showed that warfarin dose increased with the number of microsatellite (CAA)n repeats in intron 6. Interestingly, the GGCX SNP in intron 6 shows the same trend, but in our material a SNP in intron 2 was the best predictor of warfarin dose.…”
Section: Wadelius Et Almentioning
confidence: 99%
“…Today, large interindividual variability in the anticoagulant dose effect of warfarin necessitates careful monitoring and adjustment based on measurement of the prothrombin complex, particularly at the initiation of therapy. It has been shown that combinations of genetic variants in the CYP2C9, factor VII, and prothrombin genes contribute to 50% of the interindividual variance in the warfarin sensitivity (12 ). From a clinical pharmacologic perspective, combined genotype analysis before initiation of therapy could reduce bleeding complications by identifying potential low-dose responders.…”
mentioning
confidence: 99%
“…The high-dose and low-dose haplotypes can be identified in patients by screening a small number of polymorphisms (haplotype tag SNPs) [1]. Previously, factors such as CYP2C9 genotype have also been described as predictors for warfarin dose [4,5]. VKORC1 haplotype accounts for 21-25% of the variation in warfarin dose, and adding CYP2C9*2 and *3 genotypes improved the prediction model to 31% [4].…”
mentioning
confidence: 99%